Artificial intelligence as a potential subject of property and intellectual property relations - Nekit, Kateryna; Tokareva, Vira; Zubar, Volodymyr (Ius Humani. Jornal do direito, 2020)
The article analyzes the possibility to provide legal capacity to artificial intelligence, which would lead to the emergence of a new subject in legal relations. The aim of the article is to reveal whether it is possible to recognize, that artificial intelligence is able to have property and intellectual property rights. To achieve this aim, dialectical, comparative, dogmatic and legal methods are used. It is noted that according to recent studies, there are more and more grounds for recognizing artificial intelligence as subjects of legal relations. Particular attention in the article is paid to the specifics of the status of artificial intelligence in property relations. The consequences of empowering artificial intelligence with the right to property are analyzed. The conclusion is drawn on the appropriateness of such an approach, since this will solve the problem of liability for damage caused by artificial intelligence. The possibility of endowing artificial intelligence with property on the basis of trust before resolving the issue of its legal personality is proposed. Modern approaches to the problem of rights to objects of creativity created by artificial intelligence are considered in the article. The options for the distribution of rights to such objects are analyzed depending on the degree of human participation in their creation and on the level of complexity of the artificial intelligence that creates these objects. The general conclusion is made about the possibility to qualify artificial intelligence as a subject of legal relations, in particular, of property and intellectual property relations.